IntCal, SHCal, or a Mixed Curve? Choosing a 14C Calibration Curve for Archaeological and Paleoenvironmental Records from Tropical South America. Issue 3 (16th March 2018) - Marsh, Erik J; Bruno, Maria C; Fritz, Sherilyn C; Baker, Paul; Capriles, José M; Hastorf, Christine A
Abstract: Because the 14 C calibration curves IntCal and SHCal are based on data from temperate latitudes, it remains unclear which curve is more suitable for archaeological and paleoenvironmental records from tropical South America. A review of climate dynamics reveals a significant influx of Northern Hemisphere air masses and moisture over a substantial part of the continent during the South American Summer Monsoon (SASM). Areas affected by the SASM receive unknown amounts of input from both hemispheres, where an argument could be made for either curve. Until localized tree-ring data can resolve this, we suggest using a mixed calibration curve, which accounts for inputs from both hemispheres, as a third calibration option. We present a calibration example from a crucial period of environmental and cultural change in the southern Lake Titicaca. Given our current lack of data on past ∆ 14 C variation in South America, our calibrations and chronologies will likely change in the future. We hope this paper spurs new research into this topic and encourages researchers to make an informed and explicit choice of which curve to use, which is particularly relevant in research on past human–environmental relationships.